Geographical Indications and Trademarks Protection: Empowering MSMEs Through Advocacy, Legal Services in Indonesia, Oman, Philippines - Kurniawan, I Gede Agus; Gorda, Anak Agung Ayu Ngurah Sri Rahayu; Ezzerouali, Souad Ahmed; Tee-anastacio, Princess Alyssa; Sutrisni, Ketut Elly (Indonesian Journal of Advocacy and Legal Services, 2025)
The protection of geographical indications (GIs) and trademarks represents a crucial instrument within intellectual property law, serving not only as a mechanism of legal protection but also as a means of economic empowerment, particularly for micro, small, and medium enterprises (MSMEs). Nevertheless, the effectiveness of such protection is often constrained by limited access to legal services and advocacy. This study aims to analyze the ideal legal framework for the protection of GIs and trademarks in Indonesia, the Philippines, and Oman, emphasizing the importance of integrating legal services and advocacy to strengthen MSME empowerment. The research employs a normative juridical approach combined with comparative analysis, examining statutory provisions, institutional practices, and the legal cultures of each country. The findings reveal that the Philippines has developed a relatively ideal framework through the active role of the Intellectual Property Office of the Philippines (IPOPHL), which implements the IP Academy, Innovation and Technology Support Offices (ITSO), and the affirmative Juana Make a Mark initiative. By contrast, Indonesia and Oman continue to face challenges, as their regulatory structures remain heavily focused on administrative procedures without explicit provisions on legal advocacy. This study contributes by highlighting the necessity of embedding legal advocacy within substantive regulations and institutionalizing MSME support programs as a state obligation. It concludes that the protection of GIs and trademarks will be more effective if supported by structured and sustainable legal advocacy mechanisms. The key recommendation is for Indonesia and Oman to adopt the Philippines’ best practices, particularly the integration of advocacy and legal services into formal regulations, thereby strengthening MSME empowerment through the protection of geographical indications and trademarks.